2019
DOI: 10.19181/1561-7785-2019-00014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the older generation’s support on fertility in Russia

Abstract: The problem of fertility remains urgent for the Russian society that negatively affects the demographic situation in the country. Fertility is influenced by many economic and social factors, including the support of senior parents. Scientists give ambiguous assessment of the role of this support. The article is aimed at analyzing the impact of family support on fertility. On the basis of the study of the role of senior parents as subjects of family support there are identified the factors influencing the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Modern publications discuss often the problem of contrasting the traditional Russian families where the grandparents played the main role in children upbringing to occidental "self-sufficient" families, including only parents and children (Ibragimova, 2007). The author accentuates, that contemporary Russian grandparents become more and more the "visiting governors, " or perform a sporadic recreation activity, together with economical support of the grandchildren (Sharin & Kul'kova, 2019). It indicates some new tendencies and transformation of interactions between old grandparents and their children and grandchildren.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Modern publications discuss often the problem of contrasting the traditional Russian families where the grandparents played the main role in children upbringing to occidental "self-sufficient" families, including only parents and children (Ibragimova, 2007). The author accentuates, that contemporary Russian grandparents become more and more the "visiting governors, " or perform a sporadic recreation activity, together with economical support of the grandchildren (Sharin & Kul'kova, 2019). It indicates some new tendencies and transformation of interactions between old grandparents and their children and grandchildren.…”
Section: Discussionmentioning
confidence: 89%
“…V. I. Sharin and I. A. Kul'kova (2019) determined three types of families: traditionala large family including many generations living together, where the grandmothers and/or grandfathers take about all care of children; a mixt type of family, where the grandparents live separately, but help their children if necessary, more often economically and ordinary type, when the old generation lives separately and mostly did not help to care and to educate their grandchildren.…”
Section: The Image Of Elderly In the P Arentsmentioning
confidence: 99%
“…In Russia extended families play a major role in childcare (Teplova, 2007). A study based on data from the 2004 and 2007 waves of the Generations and Gender Programme survey found that 40 per cent of childcare services were provided informally in households, mainly by grandparents, especially in poorer and rural families (Sukhova, 2011;Sharin and Kulkova, 2019). MC can be used to cover costs of state or private preschool childcare.…”
Section: Pre-school Childcare Servicesmentioning
confidence: 99%